2016
DOI: 10.1016/j.jadohealth.2015.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Secret Society 123: Understanding the Language of Self-Harm on Instagram

Abstract: Purpose Nonsuicidal self-injury (NSSI) content is present on social media and may influence adolescents. Instagram is a popular site among adolescents in which NSSI-related terms are user-generated as hashtags (words preceded by a #). These hashtags may be ambiguous and thus challenging for those outside the NSSI community to understand. The purpose of this study was to evaluate the meaning, popularity, and content advisory warnings related to ambiguous NSSI hashtags on Instagram. Methods This study used the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
156
1
12

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 141 publications
(172 citation statements)
references
References 23 publications
(26 reference statements)
3
156
1
12
Order By: Relevance
“…Nonsuicidal self-injury content may also be easily discovered and socialized on social media, with descriptive analyses of Instagram revealing millions of posts containing self-injury content, spread through the use of ambiguous hashtags (Moreno et al 2016). The visualness of social media may make these posts particularly powerful.…”
Section: Peer Influencementioning
confidence: 99%
“…Nonsuicidal self-injury content may also be easily discovered and socialized on social media, with descriptive analyses of Instagram revealing millions of posts containing self-injury content, spread through the use of ambiguous hashtags (Moreno et al 2016). The visualness of social media may make these posts particularly powerful.…”
Section: Peer Influencementioning
confidence: 99%
“…fresh wounds on top of old scars). In a study using the hashtag #selfharmmm, a popular hashtag on Instagram for NSSI, Moreno et al (2015) identified different hashtags commonly used in association with NSSI pictures (i.e. #cat, #selfinjur-yyy, #blithe) and mechanisms at work in the network.…”
Section: Introductionmentioning
confidence: 99%
“…Despite benefits inherent in SNS platforms, they are not regulated by the same editorial standards of traditional media (Castillo, Mendoza, & Poblete, ; Moreno, Ton, Selkie, and Evans, ; O'Sullivan, and Heinonen, ; Schifferes et al., ). Although standards have been published to guide coverage of self‐injury and suicide in traditional media formats (Annenberg Public Policy Center, ; Gould, ), these standards are not reflected in the user‐generated content available on SNS platforms.…”
Section: Introductionmentioning
confidence: 99%